Circulating Histones Are Mediators of Trauma-associated Lung Injury - Abrams, Simon T. (American Thoracic Society, 2013)
Rationale: Acute lung injury is a common complication after severe trauma, which predisposes patients to multiple organ failure. This syndrome largely accounts for the late mortality that arises and despite many theories, the pathological mechanism is not fully understood. Discovery of histone-induced toxicity in mice presents a new dimension for elucidating the underlying pathophysiology. Objectives: To investigate the pathological roles of circulating histones in trauma-induced lung injury. Methods: Circulating histone levels in patients with severe trauma were determined and correlated with respiratory failure and Sequential Organ Failure Assessment (SOFA) scores. Their cause–effect relationship was studied using cells and mouse models. Measurements and Main Results: In a cohort of 52 patients with severe nonthoracic blunt trauma, circulating histones surged immediately after trauma to levels that were toxic to cultured endothelial cells. The high levels were significantly associated with the incidence of acute lung injury and SOFA scores, as well as markers of endothelial damage and coagulation activation. In in vitro systems, histones damaged endothelial cells, stimulated cytokine release, and induced neutrophil extracellular trap formation and myeloperoxidase release. Cellular toxicity resulted from their direct membrane interaction and resultant calcium influx. In mouse models, cytokines and markers for endothelial damage and coagulation activation significantly increased immediately after trauma or histone infusion. Pathological examinations showed that lungs were the predominantly affected organ with edema, hemorrhage, microvascular thrombosis, and neutrophil congestion. An anti-histone antibody could reduce these changes and protect mice from histone-induced lethality. Conclusions: This study elucidates a new mechanism for acute lung injury after severe trauma and proposes that circulating histones are viable therapeutic targets for improving survival outcomes in patients.